Overcoming Cabbage Crossing Incompatibility by the Development and Application of Self-Compatibility-QTL- Specific Markers and Genome-Wide Background Analysis - Xiao, Zhiliang; Han, Fengqing; Hu, Yang; Xue, Yuqian; Fang, Zhiyuan; Yang, Limei; Zhang, Yangyong; Liu, Yumei; Li, Zhansheng; Wang, Yong; Zhuang, Mu; Lv, Honghao (Frontiers in Plant Science, 2019)
Cabbage hybrids, which clearly present heterosis vigour, are widely used in agricultural production. CB201 and 96-100 are elite cabbage inbred lines; in this study, we crossed CB201 × 96-100, which yielded an excellent hybrid, 06-88. However, F1 seeds cannot be produced at the anthesis stage because the parents share the same S-haplotype (S57, class I). To overcome crossing incompatibility, we first introduced another highly self-compatible (SC) elite line, 87-534 (S5, class II), and performed whole-genome mapping of the quantitative trait loci (QTLs) governing self-compatibility using an F2 population derived from 87-534 × 96-100. Eight QTLs were detected, and high contribution rates (CRs) were observed for three QTLs: qSC7.2 (54.8%), qSC9.1 (14.1%) and qSC5.1 (11.2%). To overcome the crossing incompatibility, we performed rapid introgression of the self-compatibility trait from 87-534 to 96-100 using two self-compatibility-QTL-specific markers, BoID0709 and BoID0992, as well as 36 genome-wide markers that were evenly distributed along nine chromosomes for background analysis in recurrent back-crossing (BC). The transfer process showed that the proportion of recurrent parent genome (PRPG) in BC4F1 was greater than 94%, and the ratio of individual SC plants in BC4F1 reached 100%. The newly created line, which was designated SC96-100 and exhibited both agronomic traits that were similar to those of 96-100 and a compatibility index (CI) greater than 5.0, was successfully used in the production of the commercial hybrid 06-88. The study herein provides new insight into the genetic basis of self-compatibility in cabbage and facilitates cabbage breeding using SC lines in the male-sterile (MS) system.